Large-scale genome mining allows identification of neutral polymorphisms and novel resistance mutations in genes involved in Candida albicans resistance to azoles and echinocandins. (10th January 2020) - Sitterlé, Emilie; Coste, Alix T; Obadia, Thomas; Maufrais, Corinne; Chauvel, Murielle; Sertour, Natacha; Sanglard, Dominique; Puel, Anne; D'Enfert, Christophe; Bougnoux, Marie-Elisabeth
Abstract: Background: The genome of Candida albicans displays significant polymorphism. Point mutations in genes involved in resistance to antifungals may either confer phenotypic resistance or be devoid of phenotypic consequences. Objectives: To catalogue polymorphisms in azole and echinocandin resistance genes occurring in susceptible strains in order to rapidly pinpoint relevant mutations in resistant strains. Methods: Genome sequences from 151 unrelated C. albicans strains susceptible to fluconazole and caspofungin were used to create a catalogue of non-synonymous polymorphisms in genes involved in resistance to azoles ( ERG11, TAC1, MRR1 and UPC2 ) or echinocandins ( FKS1 ). The potential of this catalogue to reveal putative resistance mutations was tested in 10 azole-resistant isolates, including 1 intermediate to caspofungin. Selected mutations were analysed by mutagenesis experiments or mutational prediction effect. Results: In the susceptible strains, we identified 126 amino acid substitutions constituting the catalogue of phenotypically neutral polymorphisms. By excluding these neutral substitutions, we identified 22 additional substitutions in the 10 resistant strains. Among these substitutions, 10 had already been associated with resistance. The remaining 12 were in Tac1p ( n  =   6), Upc2p ( n  =   2) and Erg11p ( n  =   4). Four out of the six homozygous substitutions in Tac1p (H263Y, A790V, H839Y and P971S) conferred increases in azole MICs, while no effects were observed for those in Upc2p. Additionally, two homozygous substitutions (Y64H and P236S) had a predicted conformation effect on Erg11p. Conclusions: By establishing a catalogue of neutral polymorphisms occurring in genes involved in resistance to antifungal drugs, we provide a useful resource for rapid identification of mutations possibly responsible for phenotypic resistance in C. albicans .